Evaluation of a patient-centered after visit summary in primary care. Issue 8 (August 2018) - Federman, Alex D.; Jandorf, Lina; DeLuca, Joseph; Gover, Mary; Sanchez Munoz, Angela; Chen, Li; Wolf, Michael S.; Kannry, Joseph
Highlights: Introduction of a patient-centered AVS increased the number of patients receiving the document. Patients report that the modified AVS serves as a helpful reminder to take their medications. Clinicians who rated the AVS positively are more likely to provide the document to their patients. Abstract: Objective: To test the impact of a redesigned, patient-centered after visit summary (AVS) on patients' and clinicians' ratings of and experience with the document. Methods: We conducted a difference-in-differences (DiD) evaluation of the impact of the redesigned AVS before and after its introduction in an academic primary care practice compared to a concurrent control practice. Outcomes included ratings of the features of the AVS. Results: The intervention site had 118 and 98 patients in the pre- and post-intervention periods and the control site had 99 and 105, respectively. In adjusted DiD analysis, introduction of the patient-centered AVS in the intervention site increased patient reports that the AVS was an effective reminder for taking medications (p = .004) and of receipt of the AVS from clinicians (p = .002). However, they were more likely to perceive it as too long (p = .04). There were no significant changes in overall rating of the AVS by clinicians or their likelihood of providing it to patients. Conclusions: A patient-centered AVS increased the number of patients receiving it and reporting that it would help them remember to take their medications. Practice implications: Improvements in the patient-centeredness of the AVS may improve its usefulness as a document to support self-management in primary care.